The effect of ischaemia and reperfusion on discharge patterns of nociceptive afferent nerve fibres in the rat tail - Dal Mas, Ilario (My University, 2017)
In rats anaesthetised with enflurane, Iexamined.the response of coccygeal primary afferents fibres to noxious thermal and mechanical stimulation and to innocuous brushing, during transient ischaemia and reperfusion of their receptive fields on the tail. Ischaemia was induced by occluding the blood supply to the tail for 30 min using a tourniquet. I discovered four different groups of afferent fibres, distinguished by conduction velocity and modality, A{3fibres responding to both brush and pinch of their receptive fields showed decreased sensitivity to brush during both ischaemia and reperfusion; Ao fibres responding to pinch were unaffected by either ischaemia or reperfusion, C fibres responding to noxious heat (49· C) and pinch showed hypersensitivity during reperfusion, especially immediately after release of the tourniquet. Another group of C fibres, presumably chemosensitive, became more actiVA during ischaemia and exhibited a 7-fold increase in firing rate during receptive field reperfuslon in the absence of obvious stimuli. These results indicate that during reperfuslon of the rat tail following transient ischaemia, myelinated fibres do not increase their input to the CNS, while C fibres became more active and showed sensitization to noxious stimulation of their receptive fields. The enhanced CNS nociceptive activity which occurs during reperfusion consequently results from both peripheral and. central sensitization.
Keywords: Neurofibrils; Ischemia; Reperfusion injury; Rats as laboratory animals